Pengaruh Brand Trust, Brand Affect dan Brand Quality terhadap Brand Loyalty Dove di Surabaya - Tanuwijaya, Erwin; Muljani, Ninuk (Kajian Manajemen dan Bisnis, 2011)
As Indonesia's economy grows rapidly, the competition among brands becomes very tight. A strategy to create brand loyalty is considered to be more effective than to attract new potential customers. This study aims to analyze and provide evidence on the influence of brand trust, brand affect and brand quality to brand loyalty in the case of Dove brand in Surabaya. The number of respondents for this study was 150 people using non-probability sampling technique. Data analysis technique used in this study is the simple regression analysis. The results of this study suggest that brand trust, brand affect, and brand quality influence brand loyalty.